Evaluation of growth in children and adolescents after renal transplantation - Büyükkaragöz, Bahar; Bakkaloğlu, Sevcan Azime; Tuncel, Ayşe Fitnat; Kadıoğlu-Yılmaz, Banu; Karcaaltıncaba, Deniz; Paşaoğlu, Hatice (The Turkish Journal of Pediatrics, 2019)
Despite the advances in the last decades, it is well-known that optimal growth is usually not achieved in children with chronic kidney disease (CKD) even after successful renal transplantation (RTx). In this study, our aim was to evaluate growth patterns and factors affecting growth in pediatric and adolescent renal transplant recipients (RTR). Thirty-seven prevalent RTR with mean age of 17.0±2.9 years and mean post-RTx duration of 4.2±2.0 years were evaluated. Growth parameters, height velocities and factors affecting growth at the time of RTx (baseline) and in the post-RTx follow-up were also retrospectively assessed. Cumulative corticosteroid (CS) doses were calculated. Mean height and weight standard deviation score (SDS) values were negative (-1.4±1.1 and -1.2±1.5, respectively), whereas height SDS was positive in 16% of the patients. Mean weight, height, and BMI (body mass index) SDS of the RTR were significantly higher than the values at transplantation (p < 0.001 for weight and height SDS; p < 0.05 for BMI SDS). Height SDS was < -2.0 in 19% of the patients while 60% at the baseline. Main factors associated with post-RTx height SDS were pre-RTx height SDS (B: 0.448, p < 0.01) and CKD duration (B: -0.01, p < 0.05). Although it was much better than the pre-RTx period, the present study reveals that post- RTx growth was less than anticipated. As well as minimizing post-RTx CS doses and preserving graft function in the post-RTx follow-up, performing early transplantation and all efforts for minimizing pre-RTx growth deficit are crucial for an optimal post-RTx growth.
Keywords: adolescents; body mass index; chronic kidney disease; growth; renal transplantation